Biomechanical Evaluation Of Spinal Loadings During Oil-Palm Plantation Tasks - Mohamad Shaberi, Mohamad Nazhan (Universiti Sains Malaysia, 2022)
While the immediate adverse effects of work-related musculoskeletal disorders (WMSDs) related to oil palm harvesting have been well documented, its biomechanical study focusing on lumbar spinal forces is poorly understood. This study therefore aimed at comparing work postures and L5-S1 spinal loads during main oil-palm plantation tasks. Ten healthy, pain-free individuals were enrolled in this study and asked to complete three main tasks: 1) FFB loading using manual hand lifting and loading spike, 2) Fronds pruning using a chisel and 3) Fronds pruning using conventional and intervention sickle. The whole-body kinematics were recorded using a cutting-edge computerised Inertial Motion Unit (IMU) sensor to drive a digital motion captured avatar and automatic REBA scoring system. The ground reaction force will be acquired using a force plate, and the hand force will be measured using a load cell that attached to the cutting tools. With that data, a biomechanical evaluation will be done to predict the spinal compression forces and shear load at L5-S1 using 3D Static Strength Prediction Program (3DSSPP) software. Lifting using a loading spike could reduce the compression force on L5-S1, and it also shows that the lifting height does affect the compression and shear but has no significant difference in the REBA score. The fronds pruning tasks using sickle or chisel both recorded the highest peak REBA score of 12 (very high level). Both intervention and conventional sickle produce shear above the NIOSH allowable limit.